Handbook of trauma - Nicol, Andrew; Steyn, Elmin (Cape Town : Oxford University Press Southern Africa, 2010)
The Handbook of Trauma for Southern Africa is an invaluable resource for medical staff dealing with trauma patients in a rural or urban setting. Doctors, primary health care workers, nurses, medical students and emergency medical services personnel will benefit from the practical approach to trauma in southern Africa. The text is clearly presented for quick reference, with drawings and other figures to further elucidate the subject matter.The second edition of the Handbook of Trauma for Southern Africa is fully updated to reflect advances in the field, and includes new chapters on HIV in the trauma setting and nutrition for the trauma patient. In addition, there is broader coverage of topics such as abdominal compartment syndrome and trauma scoring systems.
Improved and updated by trauma experts to reflect the latest treatment recommendations.
Includes bibliographical references and index.
Keywords: Traumatology -- South Africa -- Handbooks, manuals, etc; Emergency medicine -- South Africa -- Handbooks, manuals, etc; Wounds and injuries -- Treatment -- South Africa -- Handbooks, manuals, etc; Print books